Rancang Bangun Sistem Informasi Website Desa Aekkorsik untuk Meningkatkan Aksesibilitas dan Layanan Digital Masyarakat - Ramadhani Fitri Panjaitan; Weny Nur Afdilla Simangunsong; Zulfa Ar Rahman; Khairul Saleh (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
the village level. Aek Korsik Village, located in Aek Ledong Subdistrict, Asahan Regency, does not yet have an official website as an information medium or a platform for digital public services. This condition limits the community’s access to village information and keeps administrative services in a conventional, manual system. Through the Community Service Program (Kuliah Kerja Nyata/KKN) Group 5, Faculty of Engineering, Universitas Asahan, a web-based information system was designed and developed for Aek Korsik Village with the aim of improving information accessibility, village government transparency, and the efficiency of digital services for the community. The system development process involved field observations, interviews with village officials, needs analysis, user interface design, implementation, and website testing. The developed village website provides key features such as village profile, news and announcements, online administrative services, and information on village potential. The implementation results show that the website serves as an effective communication medium, facilitates community access to information, and supports transparency in public services. This study also recommends further development, such as mobile application integration and enhanced system security, to ensure the sustainability of digital services in Aek Korsik Village